2020
DOI: 10.3390/agronomy10091320
|View full text |Cite
|
Sign up to set email alerts
|

Clinoptilolite Zeolite on Tropical Peat Soils Nutrient, Growth, Fruit Quality, and Yield of Carica papaya L. cv. Sekaki

Abstract: Papaya cultivation on nutrient deficient acidic peat soils causes poor growth, yield, and fruit quality of this crop. Alkalinity and the high affinity of clinoptilolite zeolite (CZ) for macronutrients could improve pH, nutrient availability, and papaya productivity on peat soils. A one-year field experiment was conducted to determine the effects of CZ on: (i) soil ammonium, nitrate, P, and K, and (ii) growth, yield, and fruit quality of papaya grown on a peat soil. Treatments evaluated were: (i) different amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…Tidak semua lahan gambut dapat dimanfaatkan untuk usaha pertanian sehingga diperlukan upaya-upaya untuk meningkatkan kualitas tanah gambut sehingga pertumbuhan dan produktivitas tanaman meningkat (Balitbangtan, 2016). Menurut Choo et al (2020) lahan gambut sangat berpotensi untuk ditanamani tanaman pangan seperti padi. Tanah gambut berpotensi untuk dibudidayakan karena mengandung bahan organik dan ketersediaan airnya tinggi.…”
Section: Abstrakunclassified
“…Tidak semua lahan gambut dapat dimanfaatkan untuk usaha pertanian sehingga diperlukan upaya-upaya untuk meningkatkan kualitas tanah gambut sehingga pertumbuhan dan produktivitas tanaman meningkat (Balitbangtan, 2016). Menurut Choo et al (2020) lahan gambut sangat berpotensi untuk ditanamani tanaman pangan seperti padi. Tanah gambut berpotensi untuk dibudidayakan karena mengandung bahan organik dan ketersediaan airnya tinggi.…”
Section: Abstrakunclassified
“…High nutrient availability under optimized nutrient management may promote crop growth [44]. In order to improve its fertilizing potential and increase its yield-forming effects, acid peat can be enriched and deacidified with the use of Ca fertilizers, NPK, zeolite, calcined clay, and diatomaceous earth [31,[34][35][36]. However, the demand for acid horticultural substrates has been growing steadily for several reasons.…”
Section: Chemical Changes In Acid Peatmentioning
confidence: 99%
“…This substrate is used in the cultivation of horticultural crops and ornamental plants, as well as forest farming. Various peat refining methods are being developed to increase its yield-forming effects, including the addition of calcium (Ca) fertilizers, mineral NPK fertilizers, zeolite, calcined clay, and diatomaceous earth [31,[34][35][36]. Our previous study demonstrated that deacidified peat can be enriched with mealworm frass [37].…”
Section: Introductionmentioning
confidence: 99%
“…Clinoptilolite zeolite (CZ) is a type of zeolite that is hydrated in nature and is widely used in agriculture. Soil physical and chemical properties have been shown being improved with the addition of CZ, especially on acidic soil and peat areas [7]. The addition of zeolite increases the water holding capacity as well as mineral fertilizers efficiency [8].…”
Section: Introductionmentioning
confidence: 99%